2013
DOI: 10.1159/000346723
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Toxicity Is Reduced by Acetylcholinesterase Inhibition in the Developing Rat Brain

Abstract: The cholinergic anti-inflammatory pathway is a neural mechanism that suppresses the innate inflammatory response and controls inflammation employing acetylcholine as the key endogenous mediator. In this study, we investigated the effects of the cholinergic agonists, physostigmine and donepezil, on neurodegeneration, inflammation and oxidative stress during oxygen toxicity in the developing rat brain. The aim of this study was to investigate the level of neurodegeneration, expression of proinflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…As acetylcholinesterase is rapidly modulated under a variety of stress conditions and is induced during cell death [26,5154], we investigated the regulation of AChE activity after administration of the non-competitive NMDA receptor antagonist MK801 (0.5 mg/kg at 0, 8, and 16 h) and the AChE inhibitor physostigmine (100 μg/kg at 0 h) to the immature rat brain. A marked up-regulation of AChE activity in brain hemispheres of rat pups at 6 (47.63 + 0.24 U/mg protein), 12 (43.50 + 1.87 U/mg protein) and 24 h (46.13 + 1.92 U/mg protein) after the last MK801 treatment (dark grey bars) was detected (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As acetylcholinesterase is rapidly modulated under a variety of stress conditions and is induced during cell death [26,5154], we investigated the regulation of AChE activity after administration of the non-competitive NMDA receptor antagonist MK801 (0.5 mg/kg at 0, 8, and 16 h) and the AChE inhibitor physostigmine (100 μg/kg at 0 h) to the immature rat brain. A marked up-regulation of AChE activity in brain hemispheres of rat pups at 6 (47.63 + 0.24 U/mg protein), 12 (43.50 + 1.87 U/mg protein) and 24 h (46.13 + 1.92 U/mg protein) after the last MK801 treatment (dark grey bars) was detected (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since we have recently demonstrated a neuroprotective effect of physostigmine in a neonatal rat model of oxygen toxicity [26] we investigated whether this pharmacological intervention might also regulate mechanisms of NMDA receptor-induced neurodegeneration. Physostigmine is used especially for treatment of myasthenia gravis and glaucoma [58], reduces diisopropyl fluorophosphate-induced mortality [59] and improves survival in a model of experimental sepsis [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In hyperoxiainduced neonatal brain injury, the upregulation of AChE has been detected [72] . After 12-24 h of hyperoxia exposure to 6-day-old rat pups, pretreatment with the AChE inhibitors physiostigmin (100 μg/kg) and donezepil (200 μg/kg) resulted in the reduction of AChE activity, and IL-1β, TNF-α mRNA and protein expression as well as the amelioration of oxidative stress and neuronal cell death [102] . Dextromethorphan (DM) is an antitussive agent widely used in paediatric care [202,203] .…”
Section: Hormonesmentioning
confidence: 99%
“…It has been shown that hyperoxia triggers an increase in oxidative stress by modulating intracellular redox homeostasis, via an increase in oxidised glutathione and a decrease in reduced glutathione and heme oxygenase 1 (HO-1) as well as an increase in lipid peroxidation in the immature brain of 6-day-old rats after 2-48 h of hyperoxia [72,102] . In this model, even short exposures to nonphysiologic oxygen levels can change the balance of the ROS-dependent thioredoxin/peroxiredoxin system.…”
Section: Neurotrophins and Neurotransmittersmentioning
confidence: 99%